Acute gastric volvulus in operated cases of tracheoesophageal fistula - Joshi Milind; Parelkar Sandesh (Wolters Kluwer Medknow Publications, 2010)
A report of two neonates of esophageal atresia with tracheoesophageal fistula who had acute gastric volvulus in the postoperative period and required gastropexy after correction of the volvulus. Such postoperative complication has not been reported in the literature so far.